Mothers’ dietary diversity and associated factors in megacity Dhaka, Bangladesh - Sadika Haque; Md Salman; Md Sadique Rahman; Abu Torab M.A. Rahim; Md Nazmul Hoque (Heliyon, 2023)
Mothers in developing countries are nutritionally vulnerable due to an undiversified diet. Dietary diversity and healthy dietary patterns of mothers are necessary for the health and nutrition of both the mother and the child. Keeping these in mind, the study was designed to investigate the determinants of mothers' dietary diversity in the capital city (Dhaka) of Bangladesh. A total 613 mothers who had at least one child aged 6–59 months were surveyed in 2020. Dietary diversity (DD) was measured by 24 h recall period following the established guidelines. To explore the determinants of dietary diversity, a log linear regression model was employed. The findings revealed that the overall DD of mothers was low, with less than 15% of respondents consuming more than 5 of the 9 food groups. The study found that if a mother receives one more year of formal education, her DD, on average, would increase by 0.70%. Receiving antenatal care (ANC) for four or more times during pregnancy increases DD by 5.13% compared to mothers who receive ANC less than four times. The findings also showed that mothers with access to assets have 10.18% higher DD than mothers without access to assets. On the other hand, mothers' employment status was negatively associated with DD. Redistributing the household workload between mother and other household members can play a critical role in increasing mothers’ DD. Providing care facilities and counseling to mothers about the nutritional value of consuming different food groups can substantially improve the situation.